2005
DOI: 10.1210/en.2004-1617
|View full text |Cite
|
Sign up to set email alerts
|

A Graves’ Disease-Associated Kozak Sequence Single-Nucleotide Polymorphism Enhances the Efficiency of CD40 Gene Translation: A Case for Translational Pathophysiology

Abstract: We analyzed the mechanism by which a Graves' disease-associated C/T polymorphism in the Kozak sequence of CD40 affects CD40 expression. CD40 expression levels on B cells in individuals with CT and TT genotypes were decreased by 13.3 and 39.4%, respectively, compared with the levels in CC genotypes (P = 0.012). Similarly, Rat-2 fibroblasts transfected with T-allele cDNA expressed 32.2% less CD40 compared with their C-allele-transfected counterparts (P = 0.004). Additionally, an in vitro transcription/translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
157
2
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(174 citation statements)
references
References 42 publications
10
157
2
3
Order By: Relevance
“…Recently, our group demonstrated that the C allele of this polymorphism caused a 15-32% increase in CD40 protein expression 21 relative to the T allele. Our functional and genetic data, coupled with the strong link that the CD40 molecule and its pathway possess to the potentiation of B-cell responses, allowed us to hypothesize that increased expression levels of CD40 could predispose individuals to antibody-mediated autoimmunity, in general.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group demonstrated that the C allele of this polymorphism caused a 15-32% increase in CD40 protein expression 21 relative to the T allele. Our functional and genetic data, coupled with the strong link that the CD40 molecule and its pathway possess to the potentiation of B-cell responses, allowed us to hypothesize that increased expression levels of CD40 could predispose individuals to antibody-mediated autoimmunity, in general.…”
Section: Discussionmentioning
confidence: 99%
“…Human peripheral B cells were isolated from volunteers, as described previously. 21 Human skeletal muscle was obtained from the National Disease Research Interchange (Philadelphia, PA, USA). Human thyroidal tissue was obtained from the healthy lobe of cancerous thyroids that were excised, during surgery (kindly provided by Dr Yuri Nikiforov, University of Cincinnati).…”
Section: Patients and Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A C/T in the 5 untranslated region of CD40 located at the −1 position within the Kozak sequence (rs1883832) has been associated with CD40 protein expression. 10 Recently, CD40 (−1C/T) polymorphism was found to be associated with ACS in Chinese people. 11 In this study, we focus on identifying a genetic marker that may help refine the disruption risk profile of vulnerable atheromatous plaque.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although it was thought that if an AUG codon is flanked by R in the position of −3 and G in +4, the rest of the consensus sequence contributes only marginally [9], some exceptions were reported. CD40 is an example that contains a G in both −3 and +4 positions, neverthe-less, the C/T SNP in the −1 site of CD40 was reported to be associated with Grave's disease, probably because the protein expression levels with CT and TT genotypes were lower when compared with the levels in CC genotypes [28,29]. Based on our criteria, the transcript of GNAS belongs to the "ss" subtype, and the short ORF encoding ALEX should not be translated.…”
Section: Discussionmentioning
confidence: 99%